INFLUENCE OF FOOD PLANTS ON THE DEVELOPMENT AND MORPHOLOGICAL CHARACTERISTICS OF MYTHIMNA UNIPUNCTA (Scientific journal of the Fergana State University, 2024)
The influence of various food plants on the development and morphological characteristics of Mythimnaunipuncta has been studied. Indicators, morphometric features and coefficient of variation of the Mythimna unipunctacaterpillar feeding on Zea mays, Capsicum annuum, Rumex confertus differ. In this regard, the quality and physicalproperties of food plants are of particular importance. All morphometric indicators of Mythimna unipuncta caterpillarsdeveloped on corn are higher than those of sorrel samples, and they also differ in a high degree of pupal formation anddevelopment of butterflies from them. Despite this, the sorrel plant is important for the survival of phytophages duringperiods of nutrient shortage.